2015
DOI: 10.1111/gcb.12960
|View full text |Cite
|
Sign up to set email alerts
|

Increased evapotranspiration demand in a Mediterranean climate might cause a decline in fungal yields under global warming

Abstract: Wild fungi play a critical role in forest ecosystems, and its recollection is a relevant economic activity. Understanding fungal response to climate is necessary in order to predict future fungal production in Mediterranean forests under climate change scenarios. We used a 15-year data set to model the relationship between climate and epigeous fungal abundance and productivity, for mycorrhizal and saprotrophic guilds in a Mediterranean pine forest. The obtained models were used to predict fungal productivity f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 61 publications
3
42
1
1
Order By: Relevance
“…Our results indicated that, even though mushroom production occurred across all stand ages, maximum yield of marketed and L. group deliciosus mushrooms occurred in younger stands. This is in line with previous research on the effect of stand age on the yield of L. deliciosus and other ectomycorrhizal fungi (Smith et al, 2002;Fern andez-Toir an et al, 2006;Bonet et al, 2010;Agreda et al, 2013), although some authors have also reported high yields at different stand ages (Zamora-Martínez and Nieto de Pascual, 1995;Bonet et al, 2004;Martínez-Peña et al, 2012a). Since marketed and L. group deliciosus species are all ectomycorrhizal fungi, they may get more carbohydrates from the more photosynthetically active trees in young stands.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Our results indicated that, even though mushroom production occurred across all stand ages, maximum yield of marketed and L. group deliciosus mushrooms occurred in younger stands. This is in line with previous research on the effect of stand age on the yield of L. deliciosus and other ectomycorrhizal fungi (Smith et al, 2002;Fern andez-Toir an et al, 2006;Bonet et al, 2010;Agreda et al, 2013), although some authors have also reported high yields at different stand ages (Zamora-Martínez and Nieto de Pascual, 1995;Bonet et al, 2004;Martínez-Peña et al, 2012a). Since marketed and L. group deliciosus species are all ectomycorrhizal fungi, they may get more carbohydrates from the more photosynthetically active trees in young stands.…”
Section: Discussionsupporting
confidence: 91%
“…The models reflect the importance of not only the amount of rainfall, but also its distribution, on mushroom production. Previous research has also indicated that mushroom production is strongly related to weather conditions, especially rainfall during the autumn season (Bonet et al, 2004;Martínez de Arag on et al, 2007;Bonet et al, 2012;Martínez-Peña et al, 2012b;Agreda et al, 2015). Although previous research has reported that temperature may be another important driver of mushroom yield (Martínez-Peña et al, 2012b;Hern andez-Rodríguez et al, 2015), no significant effect of temperature was found in this study.…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations